Association between Serum 25-Hydroxyvitamin D and Abdominal Aortic Calcification: A Large Cross-Sectional Study - Tao Liu; Ronghua Zuo; Jia Wang; Bing Wang; Lifang Sun; Shasha Wang; Baoyin Li; Jianhui Yao; Conggang Huang; Yesheng Pan; Zhijian Zhu (International Journal of Clinical Practice)
In the American population, the relationship between the standardized serum 25-hydroxyvitamin D (25(OH)D) concentration and the risk of abdominal aortic calcification (AAC) is unclear. The purpose of our study was to investigate the relationship between serum 25(OH)D concentration and AAC risk. Participants from the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2014 were analyzed cross sectionally. An analysis of the relationship between serum 25(OH)D concentration and incident AAC and severe AAC (SAAC) was based on the restricted cubic spline (RCS) and multivariable logistic regression model. In addition, generalized additive models with smooth functions were used to evaluate the relationship between serum 25(OH)D concentration and the degree of AAC. Finally, a subgroup analysis was conducted. There were a total of 3,040 individuals in our study. The serum 25(OH)D concentration was divided into quartiles (Q1: 9.37–50.5 nmol/L; Q2: 50.6–67.2 nmol/L; Q3: 67.3–85.8 nmol/L; and Q4: 85.9–318.0 nmol/L); the lowest quartile served as the reference group (Q1). After adjusting for known confounding variables, compared with the lowest quartile (Q1) of serum 25(OH)D concentration, the odds ratios with 95% confidence intervals for AAC and SAAC across the quartiles (Q2, Q3, and Q4) were (1.042 (0.812, 1.338), 0.863 (0.668, 1.115), and 1.022 (0.787, 1.327)) and (1.48 (0.87, 2.52), 1.70 (1.01, 2.92), and 2.13 (1.19, 3.86)), respectively. As shown by the RCS plot, the serum 25(OH)D concentration was associated with the risk of AAC/SAAC in a U-shaped pattern (P for nonlinearity <0.05). In addition, the degree of AAC decreased at first and then increased as the serum 25(OH)D concentration increased. In conclusion, a U-shaped relationship existed between serum 25(OH)D concentration and the risk of AAC and SAAC. Consequently, the risk of AAC and SAAC may be mitigated with regular monitoring and vitamin D supplementation.